Cognitive function in healthy aging – the effects of cognitive training combined with Transcranial Direct Current Stimulation (tDCS) - Spínola, Mónica Paula Gouveia (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação